Psychiatric and medical features of near fatal asthma. Issue 3 (March 1995) - Campbell, D A; Yellowlees, P M; McLennan, G; Coates, J R; Frith, P A; Gluyas, P A; Latimer, K M; Luke, C G; Martin, A J; Ruffin, R E
Abstract : BACKGROUND–The associations between psychiatric caseness, denial, and self reported measures of handicap and morbidity due to asthma in patients suffering a near fatal attack of asthma have not been fully explored. METHODS–Seventy seven consecutive subjects who presented to Adelaide teaching hospitals with a near fatal attack of asthma were assessed with a validated semi-structured interview following discharge from hospital. RESULTS–43% of the patients scored > or = 5 on the GHQ-28 questionnaire. There was a positive correlation between GHQ-28 score and limitation to daily activities due to asthma, and between GHQ-28 score and days lost from work, school or usual daily activities, both of which were retained after adjusting for age and sex. Asthma severity did not show a clear association with GHQ-28 score. The asthmatic patients reported high levels of denial, 57% scoring more than 3 out of 5 on the denial scale of the Illness Behaviour Questionnaire. Presentation with a history of progressive respiratory distress was negatively associated with denial score. This persisted after adjustment for age and sex–that is, those with high denial scores were more likely to report presentation as sudden collapse than progressive respiratory distress. CONCLUSIONS–Psychiatric caseness (GHQ score > or = 5) is associated with high levels of morbidity in asthmatic patients who survive a near fatal attack of asthma. High levels of denial in asthmatic subjects may be life threatening. The link between morbidity associated with asthma and psychiatric features, along with other psychosocial issues, warrants further investigation. A broader paradigm than the traditional medical model should be considered when assessing patients with asthma.